VARIABEL PENENTU LIKUIFAKSI BERDASAR EKSPERIMEN DENGAN FREKUENSI SANGAT RENDAH PADA CLEAN SAND - , RINI KUSUMAWARDANI ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Indonesia as an archipelago country which lays among three active and unstable tectonic plates namely Pacific, Indo-Australian and Indian plate, it cause Indonesia known as a country with most earthquake disaster in the world. One of popular earthquake was Yogyakarta earthquake with magnitude 6,3 which struck Indonesia on May 27, 2006. An important disaster which followed earthquake is liquefaction phenomenon. Due to of Yogyakarta earthquake, in some area were founded some evidence of liquefaction occurrence such as a sand boiling and settlement. Nowadays, many researchers agreed that there are two important parameters which play in role for the soil to liquefy. They are the soil must be in fully saturated condition and the earthquake magnitude more than 5. In this research, the author injected two parameters above to know their contribution to the soil liquefaction occurrence. In this study, all of liquefaction testing series were carried out by cyclic triaxial machine testing in order to obtain a comprehensive result of liquefaction phenomenon. All of testing used cyclic strain controlled method. In this research, the testing parameters are the saturated and unsaturated soil, soil depth (in correlation to Ï3), relative density (Dr), loading frequency (f), effective confining stress (Ï3), time delay interval of dynamic loading (Ît) and also matric suction (s). This research suggest two main conclusion, firstly, the liquefaction phenomenon occurred on soil mass during loading repetition applied on very low frequency (f = 0.1 Hz) if minimum cyclic shear strain (Î³Îµ) amplitude was 1.6% in loose condition. Second, the liquefaction indication also occurred on unsaturated clean sand (85% â¤ Sr â¤ 100) at very low frequency (f = 0.1 Hz) when meet following requirements : a soil mass on loose condition (Dr = 25%), a minimum cyclic shear strain (Î³Îµ) amplitude was 1.6% for degree saturation (Sr) â¥ 98%, while the soil mass with the degree of saturation of 85% â¤ Sr â¤ 98 %, it need minimum Î³Îµ applied at 3.2 % . For the soil mass with the degree of saturation ( Sr ) â¤ 85 %, it did not undergo liquefaction potential . Keyword : liquefaction, shear strain controlled method, matric suction, loading repetition